Complete Sternal-Sparing Approach Improves Outcomes for Left Ventricular Assist Device Implantation in Patients With History of Prior Sternotomy. Issue 1 (February 2020) - Ayers, Brian; Sagebin, Fabio; Wood, Katherine; Barrus, Bryan; Thomas, Sabu; Storozynsky, Eugene; Chen, Leway; Bernstein, Wendy; Lebow, Brandon; Prasad, Sunil; Gosev, Igor
Objective: Early reports of less invasive techniques for left ventricular assist device (LVAD) implantation have demonstrated promising results. We sought to investigate the safety and feasibility of implementing the complete sternal-sparing (CSS) approach for LVAD implantation in patients with a history of prior cardiac operation. Methods: This was a retrospective review of prospectively collected data for all patients implanted with a fully magnetically levitated LVAD from April 2017 through December 2018. Patients were dichotomized based on surgical approach: CSS or full median sternotomy (FS). Perioperative complications and overall survival were compared between cohorts. Results: Of the 29 eligible patients, 15 (52%) were implanted via the CSS approach and 14 (48%) via FS. Preoperative characteristics were similar between cohorts. Overall survival to discharge was 93% for CSS compared to 71% for FS ( P = 0.169). The CSS cohort demonstrated fewer postoperative complications, including fewer cases of severe right ventricular failure ( P = 0.006) and less blood product utilization ( P = 0.015). Median hospital length of stay was significantly shorter for the CSS cohort (median 13 vs 32.5 days, P = 0.016). Neither cohort had any 30-day readmissions. Conclusions: Early data suggest that the CSS technique is a safe and effective technique for patients with a history of prior sternotomy. Further studies are needed to validate this single-center experience.